PENGARUH MUTASI TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN ROKAN HULU - Hasibuan, Nurhayani (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
Mutations are the activities of the leadership of the organization to move the work performance is considered equivalent or equal. Adapaun mutations benefit is in addition to filling vacancies or vacancy in a place is also very beneficial for employees to improve employee performance, can also add insight and knowledge and reduce boredom on the job is practiced.This study aims to determine how the mutation employee policies, employee performance and the effect of mutations on the performance of employees in the Office of the Regional Planning Board Rokan Hulu.Penelitiaan is implemented by taking the place / location of research in the Office of Regional Planning Agency Rokan Hulu. Population of 59 Civil Servants. techniques used in the determination of the number of samples using the entire census population sampled. Types and sources of data used are qualitative data and quantitative data. Data sources include primary data and secondary data. Data collection techniques used observation, interviews, documentation and questionnaires. The analysis used is simple linear regression analysis.The effect of mutations on the performance of employees in Regional Development Planning Board Rokan Hulu turns out there is a positive relationship, which changes the value of the category of mutation followed by changes in the value of employee performance category. The results showed that the mutation has a significant influence on employee performance, but the relatively small level of significance. These results indicate that each increase of 1% variable mutation causes an increase in performance by 3%